Cellulose Isolation From Oil Palm Empty Fruit Bunch Using Different Pretreatment Processes - Novian Wely Asmoro; Chusnul Hidayat; Teguh Ariyanto; Ria Millati (Journal of Applied Science and Engineering, 2023)
A pretreatment process is needed in the bioconversion of oil palm empty fruit bunch (OPEFB) to remove lignin and to get crystalline cellulose for CNC production. Several pretreatment methods were studied, i.e., pretreatment with 10% NaOH, combination method of 10% NaOH and H2O2 (1.5% and 24%), as well as 10% NaOH and NaClo2 (1.4% and 12%). In the combination method, washing was applied in between processes to reach the pH of ± 6. The temperature for the pretreatment processes was 70 ◦C. The pH for pretreatment with 10% NaOH was ± 13, the pH for pretreatment with H2O2 (1.5% and 24%) was ± 8 and ± 6, and the pH for pretreatment with NaClO2 (1.4% and 12%) was adjusted to 4. The results showed that the highest lignin removal of 100% and the highest whiteness index were obtained after the combination pretreatment with 10% NaOH and 12% NaClO2. The highest cellulose yield of 65.33% was obtained after pretreatment with 10% NaOH. The combination pretreatment with 10% NaOH and 1.4% NaClO2 produced the highest crystallinity index of 69.35% from the cellulose obtained. The X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy results confirmed the presence of the cellulose obtained. Based on the value of the crystallinity index and considering the values of lignin removal, whiteness index, and cellulose yield, the combination pretreatment with 10% NaOH and 1.4% NaClO2 was selected as the suggested process.